Cinema 4D R19 Essential Training: Motion Graphics. - Needham, Andy (linkedin.com, 2017)
Learn how to use Cinema 4D R19 in a motion graphics workflow. Learn key foundational concepts, such as spline modeling, lighting, and materials.